Feed the Future Zimbabwe mechanization and extension activity FY 2025 Quarter One Report: October 1, 2024 - December 31, 2024 - International Maize and Wheat Improvement Center (International Maize and Wheat Improvement Center, 2024)
This is the Financial Year 2 (FY2) annual report covering October 2023 to September 2024 of the Feed the Future Zimbabwe Mechanization and Extension Activity, funded by USAID/Zimbabwe under the contract AID-BFS-IO-17-00005 and implemented by the International Maize and Wheat Improvement Center (CIMMYT) in cooperation with its subcontractor. The FY2 annual report outlines key achievements by the Mechanization Activity in its quest to improve smallholder farmers' land and labor productivity and income and reduce drudgery through mechanization. Major efforts focused on establishing service providers, increasing awareness and demand for mechanization, promoting irrigation solutions, and facilitating access to finance.